Pengaruh Brand Awareness Terhadap Loyalitas Pelanggan Pada Konsumen Semen Tiga Roda - Valenfani, Chandrika Febri; Megawati, Liya (Peneliti.net, 2024)
This study aims to examine the effect of Brand Awareness on customer loyalty. The research was conducted on 100 respondents of Semen Tiga Roda consumers who were taken by simple random sampling technique and given a 16 statement questionnaire with a Likert scale to measure responses to research variables. This study conducted the Classical Assumption Test, Hypothesis Testing with the t test, and the Coefficient of Determination. The results showed that there was a significant influence between Brand Awareness and customer loyalty